Eksplorasi Etnomatematika Batik Ngawi untuk Mengungkap Nilai Filosofi dan Konsep Matematis - fathikhin, nurul; Wijayanti, Pradnyo (Journal Intellectual Sufism Research (JISR), 2020)
Ethnomathematics is mathematics that is developed and applied by certain cultural groups by local culture by considering other knowledge, one of the cultures that developed in Ngawi is Batik. The purpose of this study was to obtain a description of the ethnomathematics of Ngawi batik in UMKM Widi Nugraha and a description of the use of ethnomathematics in Ngawi's typical batik in mathematics learning. To achieve these objectives, researchers used qualitative research methods with ethnographic methods. The results show that Ngawi batik has several philosophical values, namely the history of the name Ngawi which is reflected in Ancient Human batik with a combination of bamboo motifs, preservation in the discovery of ancient fossils stored in the Trinil museum reflected in the batik motifs of Early Man and Batik Kawung Gading, as well as there are flora and fauna found in Ngawi such as, Srigati Series batik and, Teh Jamus batik. In terms of the use of ethnomathematics, namely as a source of information on the batik tradition of the Ngawi community and can be used as a reference in designing realistic mathematics learning in schools. This learning material is in the form of material on symmetry, transformation, and congruence